Dose-dependent muscle relaxant activity of avocado leaf (Persea americana Mill.) extract: Central nervous system effects in mice and implications for phytopharmaceutical development - Nur Ahya Alsabianti; Dian Febrianti Putri Nampe; Ririn Arianti; Ihda Durratunnafisa; Raasikhah Aadilah Satria; Resky Wahyuni; Wa Ode Kezya Azhara; Nurjannah Nurjannah; Agniatul Azizah Jufri; Andi Utari Prasetya Ningrum (Priviet Social Sciences Journal, 2025)
Avocado leaves (Persea americana Mill.) contain flavonoids, saponins, and phenols, which are thought to exert muscle-relaxing effects through central nervous system depressant mechanisms. This study investigated the muscle-relaxing effects of avocado leaf extract (Persea americana) in male mice. Nine male mice were divided into three groups and administered 1%, 2%, and 4% avocado leaf infusions orally. Motor activity and reflex responses were observed every 15 min until the 100th min to assess muscle relaxation effects. The results showed that the muscle-relaxation effect increased with increasing extract concentration, at 15.55%, 34.44%, and 42.22%, respectively. Flavonoids and saponins are thought to play a role in increasing GABA activity, which reduces muscle tone. Avocado leaf extract showed muscle relaxation effects that increased with dose and has the potential to be a natural muscle relaxant through GABA activation.